Development of A STEM-Integrated Guided Inquiry E-Module on Global Warming to Enhance Students’ Conceptual Understanding - Lailatul Rahmi; Ratnawulan Ratnawulan; Ardian Fachreza (Universitas Negeri Semarang, 2026)
This study developed a Guided Inquiry-Based Electronic Module (E-Module) on Global Warming integrated with STEM to enhance students' conceptual understanding. This is a design-based research with three stages: introduction, prototyping, and assessment. The Plomp model was used for development. The third stage involved high school students in Indonesia. The E-Module was rated Highly Valid with an overall Aiken score of V, indicating excellent content and construct validity. The practicality test was rated highly practical by both teachers and students, meaning it was easy to use and understand. The quasi-experimental findings demonstrated significant improvements in conceptual understanding with large effect sizes. This reduced misunderstandings and promoted correct understanding. Results showed that the experimental group performed significantly better than the control group, indicating that the intervention was effective in promoting conceptual change. This study offers an empirical foundation for the synergistic integration of guided inquiry-based learning and STEM education through a digital platform. Once validated, this framework allows for the use of this approach to address complex scientific concepts and demonstrates its utility in educational contexts.